Adoption of a new payment method: Theory and experimental evidence - Jasmina Arifovic; John Michael Duffy; Janet Hua Jiang (Bank of Canada, 2017)
We model the introduction of a new payment method, e.g., e-money, that competes with an existing payment method, e.g., cash. The new payment method involves relatively lower per-transaction costs for both buyers and sellers, but sellers must pay a fixed fee to accept the new payment method. As a result of the network effects, our model admits two symmetric pure strategy Nash equilibria. In one equilibrium, the new payment method is not adopted and all transactions continue to be carried out using the existing payment method. In the other equilibrium, the new payment method is adopted and completely replaces the existing payment method. The equilibrium involving only the new payment method is socially optimal as it minimizes total transaction costs. Using this model, we study the question of equilibrium selection by conducting a laboratory experiment. We find that, depending on the fixed fee charged for the adoption of the new payment method and on the choices made by participants on both sides of the market, either equilibrium can be selected. More precisely, a lower fixed fee for sellers favors very quick adoption of the new payment method by all participants, while for a sufficiently high fee, sellers gradually learn to refuse to accept the new payment method and transactions are largely conducted using the existing payment method. We also find that an evolutionary learning model captures the dynamics of the experimental data well.
Keywords: E41; C35; C83; C92; 330; Central bank research; Digital currencies